Food habits of indian crested porcupine (Hystrix indica) (Kerr 1792), in district Bagh, Azad Jammu and Kashmir - Khan,M. B. (2022)
Abstract The Indian Crested Porcupine (Hystrix indica) is classified as an agricultural pest species. It feeds on plants and crops; hence, it is responsible for massive financial losses worldwide. The current study was conducted to assess the diet composition of Indian Crested Porcupine in District Bagh, Azad Jammu and Kashmir (AJ&K). Thus, fecal samples were collected and examined from different sampling sites. Reference slides of the material collected from the study area were prepared for identification of dietary components in fecal pellets. A total of 80 fecal samples were collected and processed. Percent relative frequencies (P.R.F.) were calculated for each plant species recovered from pellets. Data revealed that Indian Crested Porcupine consumed 31 plant species in its diet, among them Zea mays (34.31±7.76) was the most frequently selected species followed by Rumex obtusifolius (15.32±2.57) and Melia azedarach (12.83±4.79). The study revealed that the greatest diversity of (n=20) plant species were consumed in summer season while minimum (n=13) species were used during winter. Among the parts of plants, stem was highly consumed in spring (57.2%) as compared to seed in fall (36.7%) while spikes and leaf were the least recovered parts from the fecal matter. The Berger-Parker diversity index showed highly diversified food (10.92) in the summer time of the year as compared to the autumn season (2.95). This study provides a baseline for the diet preference of this pest in the study area. Based on current findings, a detailed investigation on damage assessment, exploration, habitat use and management of Indian Crested Porcupine in AJ&K has been recommended.